The life cycle and field epidemiology of Uromycladium acaciae (Pucciniales) on Acacia mearnsii in South Africa. (15th April 2021) - Fraser, Stuart; McTaggart, Alistair R.; Roux, Jolanda; Nel, Johan; Potgieter, James; Shuey, Louise S.; Somchit, Chanatda; Wingfield, Mike J.
Abstract: Uromycladium acaciae has damaged plantations of Acacia mearnsii in southern Africa since 2013. Uredinia of a species of Uromycladium have been known on A. mearnsii in South Africa since the 1980s. However, the recent damage is associated with telia and spermogonia. Uredinia and telia were previously treated as conspecific with a phylogenetic species concept. However, uredinia did not form after previous artificial inoculation experiments with teliospores. Controlled studies identified the optimum conditions for basidiospore infection, but the optimum conditions for sporulation and dispersal have not been identified. To investigate the life cycle and field epidemiology of Uromycladium on A. mearnsii, spores were trapped weekly and development of disease symptoms and plant phenology were monitored monthly at three plantations. Telia and spermogonia developed independently from uredinia, and nucleotide polymorphisms between rDNA of uredinia and telia were fixed based on high throughput sequencing and PCRs. All three weather variables measured had a significant effect on teliospore abundance at two of the three sites. Teliospore abundance was greatest during trapping periods when mean relative humidity was high, mean rainfall was 4–5 mm day −1 and mean temperature was 15–16°C. Teliospore counts peaked at the end of summer, potentially the result of epidemic build‐up. Results support the hypothesis that despite sharing a most recent common ancestor, uredinia on A. mearnsii in southern Africa are independent to the life cycle of the telial rust, which likely constitutes a new introduction. Furthermore, teliospores of U. acaciae disperse under wet conditions, and the wet season between October and March is the optimal period for wattle rust development. Abstract : Field observations combined with rDNA data suggest two lineages of Uromycladium ( Pucciniales ) infect Acacia mearnsii in South Africa: a highly damaging one that produces spermogonia and telia on immature host tissues and a less damaging one that produces uredinia mostly on mature tissues. Teliospore counts of the telial lineage peaked towards the end of the wet summer season, likely the result of epidemic build‐up. Spore trapping indicated that water was important for dispersal of teliospores: abundance was greatest during periods when mean relative humidity was high, mean rainfall was 4–5 mm day −1 and mean temperature was 15–16°C.